Queer and Black Martyrdom in Alan Hollinghurst and Paul Mendez - Yebra, José M. (International Journal of English Studies, 2022)
Both Alan Hollinghurst and Paul Mendez address the vulnerability of dissident, non-normative masculinities. With this purpose, I will first revise the narratives of martyrdom as an iconography (and trope) which relies on but exceeds its religious origins to understand gay and black identity representation in these writers. There are, however, some differences in their treatment of martyrdom. Hollinghurst’s career spans more than three decades and, hence, his novels feature different faces of martyrdom although all the characters/narrators do it from a white perspective. By contrast, Mendez’s Rainbow Milk revisits martyrdom as a contested narrative from the decolonized and black/queer viewpoint of the protagonist.